Knowledge management strategies for business development - Russ, Meir, 1968- (Hershey, PA : Business Science Reference, 2010)
'This book addresses the relevance of knowledge management strategies for the advancement of organizations worldwide'--Provided by publisher.
Includes bibliographical references (p. 374-406) and index.
Keywords: Knowledge management; Industrial management; Strategic planning